Microstructure and elevated temperature wear behavior of laser-cladded AlCrFeMnNi high-entropy alloy coating. (May 2022) - Zhang, Mina; Wang, Dafeng; He, Longjun; Ye, Xuyang; Ouyang, Wentai; Xu, Zifa; Zhang, Wenwu; Zhou, Xianglin
Highlights: Microstructure and phase of laser-cladded AlCrFeMnNi HEA coating were analyzed. The wear behaviour of the coatings at different temperatures was investigated in detail. The elevated temperature wear mechanisms of the HEA coating were dominated by oxidation wear and adhesive wear. Abstract: The AlCrFeMnNi high-entropy alloy (HEA) coatings were deposited on 316L stainless steel through laser cladding technology that employs pre-alloyed HEA powders. The microstructure, phase composition and hardness of the laser-cladded coatings prepared at different laser scanning speeds were investigated. The wear behavior and properties of the HEA coatings at different temperatures (from room temperature to 600 °C) was comprehensively evaluated using a pin-on-disc test. It was demonstrated that the laser-cladded AlCrFeMnNi HEA coatings exhibited dense and uniform microstructures consisting of a single BCC solid solution phase. A columnar-to-equiaxed transition structure feature was observed in the molten pool of the laser-cladded coating. The coatings possessed better high-temperature wear performance due to the protective effect of oxide films on the wear track. The coating at 400 °C exhibited the best wear resistance, which had the lowest friction coefficient and wear rate of 0.48 and 1.246 × 10 −4  mm 3 /N · m, respectively. At room temperature, the main wear mechanism of the coating was abrasive wear. However, the predominant wear mechanism at high temperatures was oxidation and adhesive wear.